Analysis of Internet Addiction Using Internet Addiction Diagnostic Questionnaire (KDAI) among First-Year Medical Students at Cenderawasih University, Papua Province. - Rumboirusi, Ricky Lazarus; Samay, Izak Yesaya (PT FORMOSA CENDEKIA GLOBAL, 2026)
Internet addiction (IA) is an addiction that is increasingly experienced by the community, especially teenagers and young adults. Papua, as a disadvantaged region, faces various challenges, ranging from infrastructure backwardness, high illiteracy rates, and low quality of education. On the other hand, internet access is improving.The purpose of this study was to examine internet addiction specifically among first-year students at the Cenderawasih Faculty of Medicine, who are under 20 years of age. Of course, the research respondents complied with the provisions of the Internet Addiction Diagnostic Questionnaire (KDAI). This study found that 26.3% of students experienced internet addiction. Students need internet guidance or a supportive learning system to minimize the risk of internet addiction (IA).